SIMPLE ONE-STEP SYNTHESES OF HETEROCYCLIC SYSTEMS FROM 2-PHENYL-4- THIENYLMETHYLIDENE-5(4H)-OXAZOLONE (Biological Sciences - PJSIR, 2003)
The title compound 1a was synthesised and its (Z)-configuration was assigned. The present investigation was intended to study the behavior of 1a towards nitrogen, carbon and oxygen nucleophiles. Thus, treatment of 1a with p-toluidine in ethanol and/or acetic acid afforded the thienylaminomethylidene-5-(4H)-oxazolone 2 and alkenamide 3 together with the imidazolinone 4, respectively. Hydrazinolysis and azidolysis of 1a resulted in the vinylthiophene derivatives 5a,b and the tetrazole 8. The triazine 6 and oxadiazinone 7 were obtained upon the effect of phenylhydrazine and hydroxy- lamine on 1a respectively. When compound 1a was allowed to react with carbon nucleophiles namely, phenylmagnesium bromide and/or dry benzene under Friedel-Crafts conditions, it gave the acylated product 9 whereas the ester 10 was obtained from the reaction of 1a with sodium ethoxide. In the absence of aromatic hydrocarbon and in acetylenetetrachloride as inert solvent containing anhydrous AlCl3, 1a underwent intramolecular alkylation and/or acylation to afford the respective thieno [3, 2-c] pyridine 11 and cyclopentadieno [b] thiophene 12.